Some Observations on the kapudans in the Ottoman Northwestern Frontier Area 16-18 c. - Moačanin, Nenad (Array, 1999)
The system of Ottoman kapudanliks in Bosnia and Croatia has evolved from the early genuine captancies on waterways into an institution predominantly based on local forms of muslim militia defence organization plus some Vlach and Habsburg military influences.